Association of ulcerative colitis and IgA nephropathy: A case report - Boulajaad, S; Haida, M; Errami, Ait; Oubaha, S; Samlani, Z; Krati, K (Global Journal of Medical and Clinical Case Reports, 2021)
The extradigestive manifestations of chronic inflammatory bowel disease most often affect the articulations, skin, eyes, liver and bile ducts. Renal involvement is rare, and manifests as kidney stones, glomerulonephritis, tubulointerstitial nephritis, and secondary amyloidosis. In this context of chronic inflammatory bowel disease, in particular ulcerative colitis, renal involvement is very often secondary to nephrotoxicity of the basic treatment of digestive pathology, and very rarely an authentic extradigestive manifestation of intestinal disease.